Unraveling the interplay between mesenchymal stem cells, gut microbiota, and systemic sclerosis: therapeutic implications - Lili Zhang; Hui Wang; Lu Zhao; Jin Zhang; Wenchang Sun; Jinjin Chu; Haobin Zhao; Chunjuan Yang; Shushan Yan; Xiaohua Chen; Donghua Xu (Microbiology Spectrum)
ABSTRACT Systemic sclerosis (SSc) is an autoimmune disease with progressive fibrotic disorders in multiple organs. Mesenchymal stem cells (MSCs) have shown great potential in treating SSc, but the exact regulatory mechanism is not fully understood. In this study, we used human umbilical cord-derived MSCs (hUC-MSCs) to treat SSc mice induced by bleomycin. The gut microbiota composition and predicted functions were analyzed using 2bRAD sequencing of fecal samples from control, SSc, and MSCs-treated mice. Treatment with MSCs improved the bleomycin-induced SSc mice, characterized by significantly reduced collagen deposition and dermal thickness. The gut microbiota of SSc mice exhibited lower species evenness and was clearly separated from the control mice based on beta diversity. MSC treatment led to a significant reduction of conditionally pathogenic bacteria enriched in SSc, including Akkermansia muciniphila and Parasutterella excrementihominis. Conversely, the relative abundance of butyrate-producing bacteria, such as Roseburia, Butyricicoccus porcorum, and Gemmiger formicilis, was notably increased in MSCs-treated SSc mice. Additionally, the functional analysis revealed that MSCs intervention effectively enhanced sulfur metabolism, tryptophan metabolism, citrate cycle, RNA polymerase, and beta-lactam resistance. In summary, the findings in the present study have suggested the close association between gut microbiota and metabolic dysbiosis in mice with SSc. The administration of MSCs has been shown to regulate the disrupted metabolic pathways in SSc mice, thus restoring the normal function of the gut microbiota. This study provides valuable insights into the specific gut microbiota and metabolic pathways involved in the efficacy of MSC treatment, thereby proposing a novel therapeutic strategy for SSc.IMPORTANCEHuman umbilical cord-derived mesenchymal stem cells (HUC‑MSCs) demonstrate efficacy in alleviating skin thickening and collagen deposition in systemic sclerosis (SSc) mice, which also regulate the gut microbiota composition and function. Specifically, MSC intervention leads to a notable increase in butyrate-producing bacteria, a decrease in Akkermansia muciniphila and Parasutterella excrementihominis, and a reversal of the dysregulated microbial function in SSc mice. These findings underscore the potential significance of gut microbiota in the therapeutic effects of MSCs in SSc.